Nitrogen retention effect of riparian zones in agricultural areas: A meta-analysis. (15th September 2021) - Lyu, Chunjian; Li, Xiaojie; Yuan, Peng; Song, Yonghui; Gao, Hongjie; Liu, Xiaoling; Liu, Ruixia; Yu, Huibin
Abstract: Nitrogen cycling in riparian zones is a complex process. Few studies have comprehensively explored the physico-chemical and biological removal of nitrogen in riparian zones. By summarizing 123 studies published between 1980 and 2020, we systematically review nitrogen removal from surface runoff, groundwater, plant uptake and microbial degradation in soil, in an attempt to comprehensively outline the nitrogen removal process in riparian zones. The results indicate that nitrogen reduction with buffer widths showed a one-phase exponential decay trend in both surface runoff ( R 2 = 0.36) and underground water ( R 2 = 0.16). At a width of 10–15 m, the average nitrogen reduction in surface runoff and underground water reached approximately 79 and 59%, respectively. In the investigation of microbial and plant nitrogen removal, denitrification rates and nitrous oxide (N2 O) emissions rates increased by 25 and 94%, respectively, in 2010–2020 compared with 2000–2010. The nitrogen uptake, denitrification, and N2 O emissions efficiency of forests were notably higher than those of grass. Warm weather is beneficial to denitrification and N2 O emissions; however, nitrogen uptake by plants showed a downward trend over the past 20 years. Environmental factors (e.g., climate, vegetation, water quality and hydrology, topography, and soil) showed notable and sensitive impacts on nitrogen retention and the microbial nitrogen cycle. In addition, legacy nitrogen had a long-term effect on waterbodies and may require an extended period to deplete and recover. This meta-analysis provides a comprehensive and scientific basis for understanding retention effects of nitrogen in riparian zones of agricultural areas. Graphical abstract: Image 1 Highlights: Comprehensive investigation of nitrogen removal processes in riparian zones. Buffer width and nitrogen reduction revealed a one-phase exponential decay trend. Higher nitrogen uptake, denitrification, and N2 O emissions in forests than grasses. Denitrification and N2 O emissions increased significant in the past 20 years.